Kandungan Minyak Atsiri Andaliman (Zanthoxylum acanthopodium DC) dan Bioaktivitasnya - Marina Silalahi; Karen Lumbantobing (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Andaliman (Zanthoxylum acanthopodium) is a species belonging Rutaceae, widely used as a spice and traditional medicine, especially by the Batak ethnic group in North Sumatra. Until now, in-depth studies on the botanical and utilization of Z. acanthopodium is limited. This study is based on literature studies on various research results published online, especially on Google scholars. Some of the keys used include: Z. acanthopodium, uses of Z. acanthopodium, essential oil of Z. acanthopodium and bioactivities of Z. acanthopodium. The ethnobotany studies of Z. acanthopodium have been used in meat and fish processing which results in a distinctive flavor and longer lasting food. In the traditional Z. acanthopodium use as mouth fresheners, dental care, treat asthma, cure rheumatism, cure coughs, ingredients for making health drinks. The Z. acanthopodium has anti-cancer and anti-microbial bioactivity associated with its essential oil. The compound of dictammine and skimmianine have anticancer activity against leukemia P-388 murine cells. The activity of Z. acanthopodium as an anti-microbial is very potential to be developed as a food preservative while preventing cancer.